A review of the ecological and socioeconomic effects of biofuel and energy policy recommendations. (August 2016) - Ji, Xi; Long, Xianling
Abstract: Many countries have attached great emphasis on biofuel because it is universally acknowledged renewable and sustainable. However, there remain doubts regarding biofuel׳s renewability, cleanliness, and ecological friendliness. In addition, its impacts on income, employment, and food security have been widely discussed. Therefore, the effect of developing biofuel as an important method of resolving the energy crisis and climate change is questioned. Based on the rocketing concern on the multiple effects of biofuel, this paper provides a comprehensive and updated review of the literature on biofuel׳s ecological effects and socioeconomic effects. The literature included in this paper is selected English language papers being published since 2004. We find that existing studies have not arrived at a consensus regarding the ecological or the socioeconomic effects of biofuel. There remain uncertainty and doubts toward biofuel׳s renewability and cleanliness. Biofuel׳s impacts on water and biodiversity are also questioned. Although biofuel is widely regarded to have positive impacts on income and employment, many studies prove that biofuel influences food security negatively. Besides, biofuel׳s economic cost is likely to be the barrier to its promotion. Because of the uncertainty of biofuel׳s impacts, this study recommends cautious attitude toward biofuel development, especially for those countries where biofuel development would be inappropriate, and suggests that policy makers engage in "demand side management" instead of unsustainable "supply side management".